2015
DOI: 10.1155/2015/234157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Patients’ Compliance to Topical Antiglaucoma Medications in Egypt as a Developing Country Model

Abstract: Purpose. To study factors affecting patients' compliance to antiglaucoma medications in Egypt where there are unique factors as a developing country. Patients and Methods. A cross-sectional descriptive study on 440 Egyptian patients with open angle glaucoma (OAG) recruited for over two years. The patients were thoroughly interviewed about their age, education level, duration of glaucoma, difficulty in instilling the drops, medication regimens, a family history of glaucoma, knowledge of the disease, and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
23
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
11
23
1
Order By: Relevance
“…The observation of this study contradicted previous reports that reported lower rate of MA among the general population of glaucoma patients. 4,15 The result of this study was however consistent with the observation of a similar study that reported 89% MA among POAG patients. 23 The traditional support system for older persons in the Nigerian society could however have played a role in this study observation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observation of this study contradicted previous reports that reported lower rate of MA among the general population of glaucoma patients. 4,15 The result of this study was however consistent with the observation of a similar study that reported 89% MA among POAG patients. 23 The traditional support system for older persons in the Nigerian society could however have played a role in this study observation.…”
Section: Discussionsupporting
confidence: 92%
“…Medication adherence in POAG is influenced by many factors including patient's socio-economic demographics, cost of AGM, difficulty in eye drops administration especially among the older persons and the side effects of the AGM. 6,15,16 The AGM are the cornerstones in the management POAG among older persons. However, the relationship between AGM utilization, patients' MA and IOP are relatively rare in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that patients with good knowledge were 2.24 times more likely adhere to their glaucoma treatment as compared to patients with inadequate knowledge. This finding was supported by studies done in Egypt [15] and Nigeria [25]. If patients know more about glaucoma and the importance of treatment to glaucoma they might be more adherent to their treatment.…”
Section: Socio-demographic Characteristicssupporting
confidence: 58%
“…33% had good adherence among a long-distance travelers (>10km) ( Table 5). to long-term therapies among patients suffering from chronic diseases in the general population [32], north India 51.66% [16] and in Egypt 46.4% [15]. However, the adherence rate of the current study was higher than other similar studies done in USA 40% [11], Iran 32.5% [5], Menelik II referral hospital(42.6%) [2] and Jima University Specialized Hospital (32.5%) [33]..…”
Section: Socio-demographic Characteristicsmentioning
confidence: 53%
See 1 more Smart Citation